The Effect of AB Mix Nutrient Formulations on The Growth and Yield of Several Red Chili Varieties in Hyroponics System - Ali, Fahri; Tiara, Dede; Rahhutami, Ratih; Yeni, Yeni; Kartina, Raida; Winata, Winata (Politeknik Negeri Bengkalis, 2024)
Hydroponics is one of the options of red chili peppers (Capsicum annuum L.) cultivation. Formulation of nutrientsolutions can be done by combining several chemical fertilizers to obtain a complete nutrient content at more cost-effective and readily accessible. The study used factorial randomized block design (RBD) in split splot. The master plots were four AB Mixformulations, F1: P (75 ppm) K (402 ppm) Ca (150 ppm) Mg (60 ppm) and S (90 ppm), F2: P (105 ppm) K (432 ppm) Ca (180ppm) Mg (90 ppm) and S (120 ppm), F3: P (135 ppm) K (462 ppm) Ca (210 ppm) Mg (120 ppm) and S (150), F4: P (165 ppm) K(492 ppm) Ca (240 ppm) Mg (150 ppm) and S (180 ppm). The subplots were 3 chili varieties; Kitavi variety (V1), Akar variety(V2) and CK F1 variety (V3). The results showed that AB Mix F4 formulation produced enhanced performance in plant height,stem diameter, crown width and fruit diameter. The use of CK curly red chili varieties exhibited better performance in theparameters of plant height, stem diameter, crown width and flowering age than the Kitavi dan Akar varieties. The AB Mix F4nutrient formulation and the use of CK curly red chili varieties are the best combination for plant growth in the variables of plantheight, stem diameter and crown width.